Occult endometrial pathologies diagnosed after sacrocolpopexy with concomitant supracervical hysterectomy for pelvic organ prolapse - Marcelle, Sarah; Nisolle, Michelle; Delbecque, Katty; Goffin, Frederic; De Landsheere, Laurent (Frontiers in Surgery, 2026)
IntroductionSacrocolpopexy with concomitant hysterectomy is a common procedure for the treatment of pelvic organ prolapse. However, occult endometrial pathologies, including malignancies, may be present in some patients, which should be considered when planning the management. The objective of this study was to determine the incidence of occult endometrial pathologies, including malignancies, in patients undergoing sacrocolpopexy with concomitant supracervical hysterectomy, and to identify associated risk factors.Materials and methodsThis was a retrospective, single-center study including all patients who underwent sacrocolpopexy with supracervical hysterectomy between November 2010 and December 2023. A total of 226 procedures were analyzed.ResultsAmong the 226 patients, 15 cases of occult endometrial pathology were identified, representing an incidence of 6.6%. These included 14 cases of endometrial hyperplasia with atypia (6.2%) and 1 case of endometrial carcinoma (0.4%). No oncological recurrence was observed after a mean follow-up period of 26 months.ConclusionsThe incidence of occult endometrial pathologies in this cohort was 6.6%. Particular attention should be given to postmenopausal patients and those with risk factors for endometrial malignancy. The use of a containment bag is recommended during specimen extraction to prevent the potential dissemination of occult malignancies. This study highlights the importance of avoiding unprotected morcellation of surgical specimens, particularly in high-risk populations.